Bcr-Abl regulates phosphatidylinositol 3-kinase-p110gamma transcription and activation is required for proliferation and drug resistance - Hickey, Fionnuala B; Cotter, Thomas G (My University, 2006)
The BCR-ABL oncogene is the hallmark of chronic myeloid leukemia, a clonal hematopoietic stem cell disorder. BCR-ABL displays constitutive tyrosine kinase activity, required for its transformation ability. Although the molecular mechanisms behind this malignancy are not fully understood, a role for phosphatidylinositol (PI) 3-kinase has been repeatedly described. Here we report the specific up-regulation of the class I(B) catalytic subunit of PI 3-kinase (p110gamma) in response to BCR-ABL expression. We demonstrate that this upregulation is due to increased transcription and is dependent on both PI 3-kinase and MEK activity. We performed in vitro kinase activity assays and show that BCR-ABL also leads to increased p110gamma activity and that this activation requires both G protein-coupled receptor and Ras signaling. In addition, by transfection of cells with dominant negative p110gamma, we determined that this specific PI 3-kinase isoform is involved in both proliferation and the apoptosis resistance associated with chronic myeloid leukemia. The data presented here define for the first time the ability of BCR-ABL to alter the expression levels of PI 3-kinase isoforms and also demonstrate a previously unreported link between BCR-ABL and p110gamma.
PUBLISHED
Keywords: leukemia